A Morphometric Analysis of the Right-sided Human Humerus’s Shaft and Nutrient Foramen - Siddique, Md Asraful Alam; Phathan, Md Azmal Khan; Karmakar, Pijush; Iqram, Towhidul; Hoshen, Md Minuddin (Eastern Medical College Journal, 2024)
Background: The term ‘morphometry’ describes the quantitative analysis of form, which includes size and shape. Additionally, it is employed in describing the shapes of various objects and in precisely locating specific locations of organs. Forensic experts and anatomists both appreciate knowing the average values of humerus segments since it aids the investigator in determining the identity of the skeleton. The nutrient foramen (NF) is important to bone formation and nutrition. Materials andMethods: This descriptive type of study was conducted in The Department of Anatomy, Sylhet MAG Osmani Medical College, Sylhet from January to December 2021with ethical clearance from respective IERB. Two hundred (200) normal adult right humerus were collected for the study purpose. Samples were collected according to the inclusion and exclusion criteria. Study variables were maximum humeral length (cm), the circumference of the middle shaft of the humerus (mm) and the number and location of the nutrient foramen. To explore the morphometry of the humerus, measurement was evaluated by using sliding vernier calipers, measuring tape, graph paper, cardboard and measuring scales. Results: Maximum humeral length was 30.33±2.11 cm and circumference of the middle shaft of the humerus was 0.72±0.05 mm. In this study 86% of humerus had single nutrient foramen and 14% had double nutrient foramen. Among them 88% of nutrient foramen belonged to Zone II, 7% to Zone I and 5% to Zone III. Conclusion: The study provides morphometric data of Right-sided Human Humerus’s Shaft and Nutrient Foramen, which will be helpful to place the various implants in the reconstructive surgery of humerus fractures and helps the anthropologists & forensic experts in identifying unknown body parts of bodies. Eastern Med Coll J. July 2024; 9 (2): 87-90